Implementation of Interpersonal Communication of The Principal of RA Al-Kautsar in Motivation of Teacher Professionalism - Alkausar Amin; Nursapiah Harahap (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The purpose of this study is to determine the principal's implementation of interpersonal communication in increasing teacher professionalism motivation at RA Al-Kautsar Jl Karya Gg. West Medan District Violation This study is a qualitative descriptive study with a naturalistic approach, collecting data through observation, interviews, and documentation studies. This study is descriptive, with four research subjects: the principal and three teachers. According to the study's findings, the use of principal interpersonal communication in improving teacher professionalism at RA Al-Kautsar Jl Karya Gg. In the West Medan Sub-district, the offenses include: 1) the use of the principal's interpersonal communication at RA Al-Kautsar Jl Karya Gg. The West Medan District has been violated on a regular and ongoing basis. Interpersonal communication between school principals and teachers takes the form of direct consultation (face to face) or the use of media (mobile phones) for assignment distribution. 2) Facilitating factors for the implementation of interpersonal communication, namely: a good communication climate between the principal and teachers, communication media availability, and each teacher's loyalty and dedication. The impediments to the implementation of interpersonal communication are: work barriers from the principal and each teacher, making it difficult to determine the right time to implement interpersonal communication..